(untitled) (Вестник КазНУ. Серия Экономическая, 2022)
Safety policies and measures in Nigeria are not encouraging as employees lose their limbs, suffer from temporary or permanent disability, or lose their lives due to insufficient arrangements for their health and safety. The study aims to examine the effect of occupational health and safety policies on employees’ performance in Chi (Ajanla) Farms. Two hypotheses were postulated and tested. First, the study adopted the descriptive research design. Multi-stage sampling method was adopted. Firstly, four departments directly involved in critical safety tasks and highly exposed to a hazardous work environment were selected. Secondly, the stratified sampling method was used to group the entire staff of the four departments into three strata (Management, senior, and junior staff). Finally, simple random sampling method was used to pick 105 respondents for the study. Data collected were analyzed using descriptive and inferential statistics. The study reported that occupational health and safety policies significantly influenced employee performance in agro-allied industries in Oyo State, Nigeria. Also, safety training has a significant and positive effect on employees’ job performance. The study concluded that occupational health and safety practices affect employees’ performance. It was recommended that the Management of Chi-Farms should ensure that occupational health and safety policies are taken seriously. training programs should be evaluated consistently to ensure that necessary and adequate measures are taken to improve safety from time to time. Key words: Employee’s Job Performance, Occupational Health And Safety Policies, Risk Assessment, Safety Training.